1980
DOI: 10.1111/j.0033-0124.1980.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Monthly Precipitation Distribution: A Comparative Index

Abstract: Zarys treści. Opracowanie zawiera analizę sezonowości odpływu w 12 zlewniach karpackich. Do badań wykorzystano szeregi dobowych przepływów z lat 1951-2010. Dla badanych przekrojów wodowskazowych obliczono: indeks sezonowości odpływu (IS), wskaźniki: pory koncentracji odpływu (WPK) i koncentracji odpływu (GMO) oraz terminu połowy odpływu (TPO), a także współczynniki ich zmienności wieloletniej i korelacji wzajemnej. Analiza pozwoliła wykryć szereg prawidłowości w ich rozkładzie przestrzennym i dynamice wielolet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
335
0
39

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 516 publications
(376 citation statements)
references
References 8 publications
2
335
0
39
Order By: Relevance
“…The 40 indexes considered in order to test the changes in the daily precipitation series are shown in Table I. Since the Precipitation Concentration Index (PCI) represents how precipitation is distributed over the year, it is worth some further explanation (Oliver, 1980). In the study, the PCI is evaluated with the modified expression of De Luis et al (2000).…”
Section: Daily Precipitationmentioning
confidence: 99%
“…The 40 indexes considered in order to test the changes in the daily precipitation series are shown in Table I. Since the Precipitation Concentration Index (PCI) represents how precipitation is distributed over the year, it is worth some further explanation (Oliver, 1980). In the study, the PCI is evaluated with the modified expression of De Luis et al (2000).…”
Section: Daily Precipitationmentioning
confidence: 99%
“…In addition, the precipitation concentration index (PCI) (Oliver, 1980), used to select the EI 30 equations most suitable for a local data set, indicated that the data of the rain gauge stations of the basin show a monthly distribution similar to that observed in Campinas, SP. The correlation between the monthly rainfall data of the Campinas station with those of the other stations used in the study showed a correlation coefficient always above 0.94.…”
Section: Estimation Of Erosivitymentioning
confidence: 95%
“…In order to estimate the aggressivity (erosivity) of rainfall, the precipitation concentration index (PCI) and the concentration index (CI), designed for measuring seasonality and daily heterogeneity, respectively, were used (Oliver 1980;Martin-Vide 2004). The PCI was calculated on a monthly rainfall basis using the equation proposed by Oliver (1980):…”
Section: Methodsmentioning
confidence: 99%
“…Also, a PCI value of 16.7 will indicate that the total precipitation was concentrated in 1/2 of the period, and a PCI value of 25 will indicate that the total precipitation occurred in 1/3 of the period. Oliver (1980) suggested that PCI values of less than 10 represent a uniform precipitation distribution or low precipitation concentration, while values between 10 and 15 indicate a moderate precipitation concentration. Values between 15 and 20 represent an irregular distribution of rainfall, while values above 20 show a strong irregularity of precipitation distribution.…”
Section: Methodsmentioning
confidence: 99%